INVESTIGATION OF THE DEUTERATION OF CRYSTALLINE LAYER FORMS OF SILICA AND ALUMINA IN LIQUID D2O - Mitsyuk B.M.; Ostapenko G.T.; Timoshkova L.P.; Komov I.L.; Pisanskaya I.R.; Pushkarev A.V.; Litovchenko A.S.; Kalinichenko E.A.; Hach-Ali P.F.; Baker J.H. (My University, 2006)
The mechanism of hydrogen-deuterium isotopic exchange was studied in crystalline layer forms of silica (hydrous and cation-substituted SiO2-X2 and SiO2-Y varieties) and alumina (hydrargillite and boehmite) in contact with liquid D2O at temperatures of 20-200°C and saturated vapor pressure. Extensive exchange was observed between adsorbed H2O and D2O molecules via the self-diffusion mechanism in all silica varieties and boehmite at a temperature of 20°C. Deuterium substitution for hydrogen in structural OH groups was observed at 20°C only in the H-form of SiO2-Y (0.7%) and boehmite (1.2 or 17% with molecular deuteration). When the temperature of the hydrothermal treatment of samples was raised up to 200°C, the degree of structural deuterium exchange increased up to 12% (35% with molecular deuteration) in the former case and up to 34% in the latter case. In the former case, the process of isotopic exchange occurred by the nucleophile substitution SNi near surface silicon atoms, and in the latter case, the electrophile substitution ENi in surface OH groups. © Pleiades Publishing, Inc. 2006.